2011
DOI: 10.1007/s00402-011-1323-4
|View full text |Cite
|
Sign up to set email alerts
|

Minimum 5-year results of focal articular prosthetic resurfacing for the treatment of full-thickness articular cartilage defects in the knee

Abstract: The device appears to be an effective reconstructive treatment option for large full-thickness cartilage and osteochondral lesions of the knee in middle-aged patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 38 publications
3
70
1
3
Order By: Relevance
“…Massive research efforts on biological solutions have been made in the last decades using expensive and sophisticated methods while showing inconsistent results 9,10,19,33 . Hence, a number of groups are exploring the FKR concept, where the first study in human knees reports promising results 34 . Our finding of minor damage on the opposing cartilage in the cases where the implant was appropriately inserted confirms that this technology might become of clinical use in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Massive research efforts on biological solutions have been made in the last decades using expensive and sophisticated methods while showing inconsistent results 9,10,19,33 . Hence, a number of groups are exploring the FKR concept, where the first study in human knees reports promising results 34 . Our finding of minor damage on the opposing cartilage in the cases where the implant was appropriately inserted confirms that this technology might become of clinical use in the future.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the longestterm study of patients managed with focal resurfacing was reported by Becher et al 16 . Twenty-one patients with a mean age of fifty-four years were followed for a minimum of five years (range, five to six years).…”
Section: Resultsmentioning
confidence: 96%
“…The authors concluded that focal resurfacing was an excellent option for the treatment of "large full-thickness cartilage and osteochondral lesions of the knee in middle-aged patients." 16 Bipolar Tibiofemoral Inlay Resurfacing Bipolar knee inlay resurfacing was introduced in 2008. The intent of this procedure is to provide an option for patients with early tibiofemoral arthrosis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have focused on the optimal position of the FMI in regard to joint pressure and implant behavior in animal models. While these studies demonstrated the congruence of the implant with surrounding cartilage to be significant in preserving physiologic joint pressure [4][5][6][7], other studies focused on the outcome and implant behavior of the different implant designs in various animal models [13][14][15]24]. A protruded implant may be a clear etiology of damage to opposing cartilage, however some animal studies also reported defects in the setting of a flat implant [4,5,24].…”
Section: Introductionmentioning
confidence: 99%